Comparative Study of Prism Octahedron Network via Eccentric Invariants. (17th March 2023) - Ali, Haidar; Abdulkhaleq Ali, Didar; Nadeem, Muhammad; Ali, Parvez; Kirmani, Syed Ajaz K.; Sesay, Mohamed
Abstract : Topological indices are empirical features of graphs that characterize the topology of the graph and, for the most part, are graph independent. An important branch of graph theory is chemical graph theory. In chemical graph theory, the atoms corresponds vertices and edges corresponds covalent bonds. A topological index is a numeric number that represents the topology of underline structure. In this article, we examined the topological properties of prism octahedron network of dimension m and computed the total eccentricity, average eccentricity, Zagreb eccentricity, geometric arithmetic eccentricity, and atom bond connectivity eccentricity indices, which are used to utilize the distance between the vertices of a prism octahedron network.